Attenuation of Rheumatoid Inflammation by Sodium Butyrate Through Reciprocal Targeting of HDAC2 in Osteoclasts and HDAC8 in T Cells - Kim, Da Som; Kwon, Jeong-Eun; Lee, Seung Hoon; Kim, Eun Kyung; Ryu, Jun-Geol; Jung, Kyung-Ah; Choi, Jeong-Won; Park, Min-Jung; Moon, Young-Mee; Park, Sung-Hwan; Cho, Mi-La; Kwok, Seung-Ki (Frontiers in Immunology, 2018)
Rheumatoid arthritis (RA) is a systemic autoimmune disease caused by both genetic and environmental factors. Recently, investigators have focused on the gut microbiota, which is thought to be an environmental factor that affects the development of RA. Metabolites secreted by the gut microbiota maintain homeostasis in the gut through various mechanisms (e.g., butyrate, which is one of the major metabolites of gut microbiota, exerts an anti-inflammatory effect by activating G-protein-coupled receptors and inhibiting histone deacetylases (HDACs)). Here, we focused on the inhibition of the HDACs by butyrate in RA. To this end, we evaluated the therapeutic effects of butyrate in an animal model of autoimmune arthritis. The arthritis score and incidence were lower in the butyrate-treated group compared to the control group. Also, butyrate inhibited HDAC2 in osteoclasts and HDAC8 in T cells, leading to the acetylation of glucocorticoid receptors and estrogen-related receptors α, respectively. Additionally, control of the TH17/Treg cell balance and inhibition of osteoclastogenesis were confirmed by the changes in target gene expression. Interleukin-10 (IL-10) produced by butyrate-induced expanded Treg cells was critical, as treatment with butyrate did not affect inflammatory arthritis in IL-10-knockout mice. This immune-cell regulation of butyrate was also detected in humans. These findings suggest that butyrate is a candidate agent for the treatment of RA.